MR-guided high-intensity focused ultrasound for noninvasive cancer treatment - Huisman, M. (e-Med, 2011)
Magnetic resonance (MR)-high-intensity focused ultrasound (HIFU) is an innovative, noninvasive tumour ablation technique. MR imaging and focused ultrasound are combined allowing real-time anatomic guidance and temperature mapping during treatment. Recently, the volumetric ablation approach has been introduced in order to reduce treatment length and provide more homogeneous tumour ablation. After successful treatment of uterine fibroids, MR-HIFU is currently being investigated for the treatment of malignant tumours. Palliative treatment of painful bone metastases is already applied in clinical practice. Several issues need to be further investigated for successful cancer treatment with MR-HIFU, including patient selection criteria, definition of treatment margins and optimal transducer technology.